Association analyses of immune and DNA repair gene polymorphisms with non-hodgkin lymphoma risk and prognosis in a multiethnic Malaysian population / Ten Lik Chin - Ten, Lik Chin (2018)
Previous large consortia efforts and genome-wide association studies (GWASs) have implicated a number of genetic variants associated with the susceptibility and prognosis of different non-Hodgkin lymphoma (NHL) types and subtypes. However most of the published studies from the Western population and rarely in Asians. Seventeen candidate single nucleotide polymorphisms (SNPs) from two major groups of NHL-associated genes: immune function SNPs [n=10; rs3832246 (T>-), rs6773854 (T>C), rs6457327 (C>A), rs9271100 (C>T), rs2647012 (C>T), rs10484561 (T>G), rs1571011 (A>C), rs1977389 (T>G), rs10887878 (T>A) and rs4985700 (A>C)] and DNA repair SNPs [n=7; rs17655 (G>C), rs861539 (G>A), rs25487 (C>T), rs25489 (C>T), rs1799782 (G>A), rs13181 (T>G) and rs1799793 (C>T)] were genotyped. A total of 1321 subjects were successfully recruited into this study which consisted of 652 NHL cases and 669 healthy controls from three major ethnic groups in Malaysia, namely the Malay (n=612), Chinese (n=533) and Indian (n=176). Genotyping was performed using TaqMan® SNP genotyping method. Associations of SNPs with NHL risk in each ethnic group were assessed by logistic regression analysis evaluating three genetic models (additive, dominant and recessive model) and adjusted against age and gender. Meta-analysis with the random-effect model was used to estimate the effect size of SNPs in combined three ethnic groups. Two human leukocyte antigen (HLA) class II SNPs: rs2647012 (C>T) and rs10484561 (T>G) showed significant association with NHL risk after Bonferroni correction (P<0.003). SNP rs2647012 (C>T) was significantly associated with reduced risk in all NHL (Padditive-adjusted=0.0008; OR=0.54; 95% CI=0.37-0.77) in Malay group and iv B-cell NHL in both pooled subjects (Padditive-adjusted=0.0008; OR=0.69; 95% CI=0.55-0.87) and Malay group (Padditive-adjusted=0.0007; OR=0.51; 95% CI=0.35-0.76). SNP rs10484561 (T>G) showed significant association with subtype FL in pooled subjects (Pdominant-adjusted=0.003; OR=2.39; 95% CI=1.35-4.22) and Malay group (Pdominant-adjusted=0.003; OR=3.50; 95% CI=1.54-7.97). Through cis-expression quantitative trait loci (eQTL) analysis, rs2647012 (C>T) and rs10484561 (T>G) showed potential regulatory function as it showed significant cis-eQTL correlation with nearby HLA class II molecule expression. Using the Kaplan-Meier method and Cox regression analysis, 130 DLBCL patients with complete clinical information were further evaluated for the association of SNPs with DLBCL prognosis. No significant association was observed between DLBCL prognosis with any of the studied SNPs. In conclusion, this study reported the association of rs2647012 (C>T) and rs10484561 (T>G) with NHL risk in the Malaysian population.